The Impact of COVID-19 Pandemic on the Developing Nations: Emerging Mental Health Challenges and Interventions - Noronha, Flavia; Pant, Sanju; Yesodharan, Renjulal; Nayak, Asha; Dsa, Rochelle (Indian Journal of Community Health, 2021)
The world is facing an unprecedented challenge of the 21st century in the form of COVID-19 outbreak. People across the culture, race, ethnicity, socio-economic background are being affected by the rippling effects of this pandemic. The aim of this narrative review is to briefly describe the impact of the pandemic on mental health, the vicious cycle of social issues and psychological health caused and aggravated by the Covid-19 pandemic. We also aim to highlight certain interventions to overcome the mental health challenges posed by the pandemic. For this purpose, a thorough search of all databases was done to gather articles relevant to the objective of this narrative review. Keywords were used in combination and separately to identify the articles on the various psychosocial issues caused by the pandemic. Published articles in various databases like Scopus, Web of Science, Pubmed etc., related to psychosocial effects due to COVID-19 were searched and summarized to justify and support the objective of this paper. The coming months will reveal the extent of damage this pandemic has caused to the socio-economic and health sectors across the globe. It is crucial to recognize the psychosocial impact of this pandemic and necessitate the measures to overcome them by mobilizing the resources we have at hand.